Influence of Peer Victimization and Self-Esteem on Child-to-Parent Violence Perpetration - Miriam Junco-Guerrero; Francisco Javier Fernández-Baena; Milagros Escobar; David Cantón-Cortés (Medical Sciences Forum, 2021)
The aim of the present study was to analyze the relationship between both peer victimization (both as a victim and a witness) and self-esteem and child-to-parent violence (CPV) towards one’s mother and father, while controlling for participants’ substance use and age. In addition, the moderating influence of the participants’ sex on those relationships was tested. A total of 855 high school students (402 female and 453 male) aged between 13 and 20 years (M = 15.29; SD = 1.10) were surveyed. Information about CPV was obtained through the Child-to-Parent Aggression Questionnaire (CPAQ). Sociodemographic data, self-esteem, and peer victimization were assessed through a self-constructed questionnaire, the Rosenberg Self-esteem Scale (RSS), and the Violence Exposure Questionnaire (VEQ), respectively. Regarding violence towards mothers, the results of the multiple regression analyses showed a relationship between suffering and the witnessing of peer victimization, which was also correlated with lower scores in terms of self-esteem. A moderating role of the aggressor’s sex with respect to self-esteem was found, wherein the relationship between self-esteem and CPV was only significant for the male participants. With regard to violence towards fathers, the results showed a relationship with witnessing peer victimization and self-esteem. In this case, a moderating role of the aggressor’s sex with respect to self-esteem and being a victim of peer violence was found, for which their relationships with CPV were only significant for male participants. The results confirm the idea that both suffering from and witnessing peer violence, as well as possessing low self-esteem levels, have an effect on the probability of CPV perpetration, which differs according to the sex of the perpetrator in the case of self-esteem.